POLYCARBONATE-SILICA NANOCOMPOSITE MEMBRANES FOR CARBON DIOXIDE SEPARATION - ABDULGADIR MUSSA, ALAMIN IDRIS (2018)
Polymeric membranes suffer permeability-selectivity trade-off challenge due to the structure-property limitation of the material. To overcome this, polymer-inorganic composites membranes are proposed for carbon dioxide (CO2) separation. In this study, polycarbonate (PC) as core polymer and silica as inorganic material were utilized to develop PC-silica nanocomposite membranes. Dense and asymmetric porous PC membranes were first fabricated by dry-wet phase inversion method using dichloromethane and N-methyl-2-pyrrolidone solvents. FESEM images show that PC/DCM membranes are dense while PC/NMP membranes are dense top layer with spongy substructure. The membranes performance was evaluated by measuring the permeance of CO2, CH4 and N2 gases at 240.5oC and pressures of 2-10 bar. The average CO2/N2 and CO2/CH4 ideal selectivities of PC/DCM membrane were found to be 25.1±0.8 and 21.1±0.6, respectively.